Cardiac dysfunction and ferritin as early markers of severity in pediatric sepsis, - Cristian T. Tonial; Pedro Celiny R. Garcia; Louise Cardoso Schweitzer; Caroline A.D. Costa; Francisco Bruno; Humberto H. Fiori; Paulo R. Einloft; Ricardo Branco Garcia; Jefferson Pedro Piva
Abstract Objective: The aim of this study was to verify the association of echocardiogram, ferritin, C-reactive protein, and leukocyte count with unfavorable outcomes in pediatric sepsis. Methods: A prospective cohort study was carried out from March to December 2014, with pediatric critical care patients aged between 28 days and 18 years. Inclusion criteria were diagnosis of sepsis, need for mechanical ventilation for more than 48 h, and vasoactive drugs. Serum levels of C-reactive protein, ferritin, and leukocyte count were collected on the first day (D0), 24 h (D1), and 72 h (D3) after recruitment. Patients underwent transthoracic echocardiography to determine the ejection fraction of the left ventricle on D1 and D3. The outcomes measured were length of hospital stay and in the pediatric intensive care unit, mechanical ventilation duration, free hours of VM, duration of use of inotropic agents, maximum inotropic score, and mortality. Results: Twenty patients completed the study. Patients with elevated ferritin levels on D0 had also fewer ventilator-free hours (p = 0.046) and higher maximum inotropic score (p = 0.009). Patients with cardiac dysfunction by echocardiogram on D1 had longer hospital stay (p = 0.047), pediatric intensive care unit stay (p = 0.020), duration of mechanical ventilation (p = 0.011), maximum inotropic score (p = 0.001), and fewer ventilator-free hours (p = 0.020). Conclusion: Cardiac dysfunction by echocardiography and serum ferritin value was significantly associated with unfavorable outcomes in pediatric patients with sepsis.